Changes in expression of growth‐associated protein‐43 in trigeminal ganglion neurons and of the jaw opening reflex following inferior alveolar nerve transection in rats. (4th March 2013) - Teramoto, Kohei; Tsuboi, Yoshiyuki; Shinoda, Masamichi; Hitomi, Suzuro; Abe, Kimiko; Kaji, Kaori; Tamagawa, Takaaki; Suzuki, Azumi; Noma, Noboru; Kobayashi, Masayuki; Komiyama, Osamu; Urata, Kentaro; et al.
<x xml:space="preserve">Abstract</x> The aim of the present study was to clarify an involvement of growth‐associated protein‐43 (GAP‐43) in the regeneration of primary afferent trigeminal ganglion (TG) neurons following inferior alveolar nerve transection (IANX). A larger number of GAP‐43 immunoreactive (GAP‐43 IR) TG neurons was observed in rats 3 d after IANX compared with sham rats. Growth‐associated protein‐43 IR TG neurons were also detected for 30 d after IANX, and the number of GAP‐43 IR TG neurons was significantly higher in the IANX model until day 30. The relative number of large (>600 μm2) GAP‐43 IR TG neurons was significantly lower, whereas the relative number of small (<400 μm2) GAP‐43 IR TG neurons was significantly higher than that at day 0 until 30 d after IANX. To evaluate the functional recovery of damaged IAN, the jaw opening reflex (JOR), elicited by the electrical stimulation of the IAN, was measured before and after IANX. Jaw opening reflex occurrence was gradually increased and the relative threshold of electrical stimulation eliciting JOR was gradually decreased over the 30‐d duration of the study. On day 30 after IANX, the JOR occurrence and relative JOR threshold were similar to those in sham rats. The present findings suggest that changes in the expression of GAP‐43 in TG neurons after IANX are involved in regeneration and functional recovery of the transected IAN.